Maternal alcohol consumption and risk of postpartum depression: a meta-analysis of cohort studies. (December 2022) - Qiu, X.; Sun, X.; Li, H.O.; Wang, D.H.; Zhang, S.M.
Abstract: Objectives: The relationship between maternal alcohol consumption and postpartum depression (PPD) is still controversial. The objective of the present study was to assess the association between maternal alcohol consumption and the risk of developing PPD by means of a meta-analysis of cohort studies. Study design: This was a meta-analysis. Methods: PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc, Chinese National Knowledge Infrastructure, Weipu, and Wanfang databases were searched up to February 4, 2021, to identify relevant studies that evaluated the association between maternal alcohol consumption and PPD. Meta-analysis was conducted using RevMan software and Stata software. Subgroup and sensitivity analyses were performed to explore the potential heterogeneity source, and Begg's funnel plots and Begg's linear regression test were conducted to assess the potential publication bias. Results: A total of 12 studies involving 50, 377 participants were identified in our study. Overall, pregnant women who were exposed to alcohol were at a significantly greater risk of developing PPD compared with those who did not consume alcohol (odds ratio = 1.21; 95% confidence interval: 1.04–1.41; P = 0.020). Conclusions: Maternal alcohol consumption is significantly associated with the risk of developing PPD. These results emphasize the necessity of enhancing health awareness, improving the public health policies and regulations concerning alcohol use, and strengthening the prevention and intervention of maternal alcohol consumption to promote maternal mental health.